ANALISIS PERILAKU KONSUMEN DALAM PENGAMBILAN KEPUTUSAN MENGKONSUMSI JENIS PRODUK BANUA COKELAT PADA INDUSTRI SA’ADAH AGENCY DI KOTA PALU - K. Jumba, Hadayani, Dafina Howara, Melida (AGROTEKBIS, 2015)
This study aim was to determine consumer behavior in making decision for the consumption of Banua chocolate product at Sa?adah Agency Industry in Palu City during October to December 2014. The study location and respondents were purposively determined.  There were 33 respondents selected. Data used were primary and secondary information. This research used Chi Square method to analyze the data. The study results showed that the financial performance of Banua Chocolate is good based on the values of X2count > X2table.   The taste quality had the value of 18.2 > 9.49, the price had that of 22.4 > 9.49, the grade had that of 27.8 > 9.49,  the job status had that of 19.8 > 9.49, and the kind of chocolate had that of 6 < 9.49. The consumers of the chocolate mostly are students and only few are workers.